2005
DOI: 10.1099/ijs.0.63276-0
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and morphological evaluation of the genera Anabaena, Aphanizomenon, Trichormus and Nostoc (Nostocales, Cyanobacteria)

Abstract: The heterocytous cyanobacteria form a monophyletic group according to 16S rRNA gene sequence data. Within this group, phylogenetic and morphological studies have shown that genera such as Anabaena and Aphanizomenon are intermixed. Moreover, the phylogeny of the genus Trichormus, which was recently separated from Anabaena, has not been investigated. The aim was to study the taxonomy of the genera Anabaena, Aphanizomenon, Nostoc and Trichormus belonging to the family Nostocaceae (subsection IV.I) by morphologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
250
2
14

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 311 publications
(308 citation statements)
references
References 32 publications
(45 reference statements)
38
250
2
14
Order By: Relevance
“…1E) in comparison to the oval, less numerous akinetes in N. spumigena. This result is in agreement with a recent morphological and phylogenetic study of various heterocytous filamentous cyanobacteria, such as Anabaena and Aphanizomenon, showing that shape, width and length of the akinetes were coherent with phylogenetic clustering (Rajaniemi et al, 2005). Strains of N. harveyana formed a separate group, which was more diverse (Figs 2, 3 and 4, Table 3).…”
Section: Phylogenetic Relationships Within the Genus Nodulariasupporting
confidence: 81%
See 2 more Smart Citations
“…1E) in comparison to the oval, less numerous akinetes in N. spumigena. This result is in agreement with a recent morphological and phylogenetic study of various heterocytous filamentous cyanobacteria, such as Anabaena and Aphanizomenon, showing that shape, width and length of the akinetes were coherent with phylogenetic clustering (Rajaniemi et al, 2005). Strains of N. harveyana formed a separate group, which was more diverse (Figs 2, 3 and 4, Table 3).…”
Section: Phylogenetic Relationships Within the Genus Nodulariasupporting
confidence: 81%
“…The greater than 97 % similarity value does not necessarily guarantee that strains share a high degree of DNA-DNA reassociation and thus are closely related (Stackebrandt & Goebel, 1994). A recent study on the 16S rRNA gene of planktonic and benthic Anabaena showed that the two forms were intermixed and shared similarities as high as 99?2 % (Rajaniemi et al, 2005). However, the strains formed several distinct clades, possibly representing different species.…”
Section: Phylogenetic Relationships Within the Genus Nodulariamentioning
confidence: 99%
See 1 more Smart Citation
“…The 16S rRNA gene sequence of Nostoc muscorum HUW 888 showed very high similarity (98?6 %) to the sequences published by Rajaniemi et al (2005) for Nostoc muscorum II and I. The 16S rRNA gene sequence of a strain affiliated to Nostoc muscorum CENA61 (GenBank accession no.…”
Section: Morphological Features Of the Studied Exsiccatamentioning
confidence: 93%
“…In the present study that focused on 12 heterocystous cyanobacterial genera and 41 cyanobacterial strains in total, the HIP primers and their resolution were found to be sufficient for estimating the phylogenetic relationships amongst heterocystous cyanobacteria. The dendrograms constructed using HIP fingerprints (HIP-AT, HIP-CA, HIP-GC, and HIP-TG) showed that the genus Nostoc was most genetically heterogeneous and advanced amongst all the 12 genera (Rajaniemi et al 2005;Svenning et al 2005;Willame et al 2006). One of the interesting features was the differential alignment of the strains Nostoc sp.…”
Section: Discussionmentioning
confidence: 99%